Pengaruh Hiv yang Mengalami UTI, HIP Dislocation, Sciatic Nerve Pain, Penggunaan Kontrasepsi Disertai Ptsd - R. Mohamad Javier; Andisa Fadhila Rialdi; Abdillah Budi Ksatria; Bima Mahardhika Aji; Budi Prakoso; Maisuri T. Chalid; Bambang Widiwanto; Mochamad Aleq Sander; Risma Karlina Prabawati; Rachmat Budi Prasetyo (Syntax Corporation Indonesia, 2023)
HIV (Human Immunodeficiency Virus) is a virus that attacks the immune system making the body susceptible to various diseases, such as TB, TORCH and others. Knowing the effect of the incidence of HIV (Human Immunodeficiency Virus) which has CD-8 T Cell maturity accompanied by UTI (Urinary Tract Infection) and Hip Dislocation with Sciatic Nerve Pain using the minipill as emergency contraception accompanied by PTSD (Post Traumatic Syndrome Disorder) in Commercial Sex Workers. This research is a Systematic Review using the Preferred Reporting Items for Systematic Reviews and Meta-analyses method or commonly called PRISMA, this method is carried out systematically by following the correct research steps or protocols. Sources were taken from the PubMed site and the Google Scholar site with journals published in 2017-2022 and then screening was carried out to obtain 20,486 results. Journal clustering was carried out and the number of Scopus Q1 indexed journals was 1 journal, 2 journals Q2, 1 journal indexed Sinta S1, so that 4 journals were extracted. The majority of journals discuss age related to the influence of HIV (Human Immunodeficiency Virus) events which experience CD-8 T Cell maturity accompanied by UTI (Urinary Tract Infection) and Hip Dislocation with Sciatic Nerve Pain using the minipill as emergency contraception accompanied by PTSD (Post Traumatic Syndrome) Disorder) in commercial sex workers.